New insight into the biocompatibility/toxicity of graphene oxides and their reduced forms on Chlamydomonas reinhardtii - Bytešníková, Zuzana; Koláčková, Martina; Dobešová, Markéta; Švec, Pavel; Ridošková, Andrea; Pekárková, Jana; Přibyl, Jan; Cápal, Petr; Húska, Dalibor; Adam, Vojtěch; Richtera, Lukáš (NanoImpact, 2023)
Graphene oxides (GOs) and their reduced forms are often discussed both positively and negatively due to the lack of information about their chemistry and structure. This study utilized GOs with two sheet sizes that were further reduced by two reducing agents (sodium borohydride and hydrazine) to obtain two different degrees of reduction. The synthesized nanomaterials were characterized using scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), elemental analysis (EA), Fourier transform infrared (FTIR) spectroscopy, and Raman spectroscopy (RA) to understand their chemistry and structure. The second focus of our investigation included in vitro testing of the biocompatibility/toxicity of these materials on a model organism, the freshwater microalga Chlamydomonas reinhardtii. The effects were studied on the basis of biological endpoints complemented by biomass investigation (FTIR spectroscopy, EA, and atomic absorption spectrometry (AAS)). The results showed that the biocompatibility/toxicity of GOs is dependent on their chemistry and structure and that it is impossible to generalize the toxicity of graphene-based nanomaterials.
Keywords: grafit; nanostruktury; Chlamydomonas reinhardtii; Reduction; Chlamydomonas; Biocompatibility; oxidy; Graphite; Nanostructures; Microalgae; Toxicity; Graphene oxide; Oxides